Review article: A scoping review of human factors in avalanche decision-making - A. Hetland; A. Hetland; R. A. Hetland; T. T. Skille; T. T. Skille; A. Mannberg; A. Mannberg (Natural Hazards and Earth System Sciences)
The interest in understanding the human aspects of avalanche risk mitigation has steadily grown over the past few decades. Between 2001–2011, 11 research papers on decision-making in avalanche terrain were published in peer- reviewed journals. Between 2012–2022, this number rose to 55. These papers have been authored by researchers from various disciplines and publications in journals across different fields. Despite the field's nascent stage, to guide future research, it is pertinent to provide an overview of the insights from the existing research literature.